A Brief Review of Krill Oil History, Research, and the Commercial Market. (1st March 2015) - Kwantes, Jonathan M.; Grundmann, Oliver
ABSTRACT: In the last few years there has been a noticeable increase in both the promotion and research of krill oil for its purported health benefits, including the management and treatment of conditions, such as hyperlipidemia, inflammation, and arthritis. Additionally, because krill oil contains the same omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) found in fish and fish oil, krill oil is viewed as a viable alternative to fish oil to deliver the health benefits associated with EPA and DHA. The following review provides an overview of the currently available 10 peer-reviewed human clinical studies on krill oil, its safety, as well as a brief summary of the commercial krill oil market.